Morphology and properties of halloysite nanotubes reinforced polypropylene nanocomposites - Du, M.; Guo, B.; Cai, X.; Jia, Z.; Liu, M.; Jia, D.
Halloysite nanotubes (HNTs)were utilized to prepare polypropylene (PP)nanocomposites by simple melt-compounding approach. Compared with other silicates such as montmorillonite and kaolinite, HNTs show much better dispersion property. The PP nanocomposites with HNTs exhibit concurrence increase in tensile and flexural strength, flexural modulus and impact toughness. Surface modification of HNTs lends the PP anocomposites higher strength, modulus and lower toughness. The increase in mechanical properties is correlated with the well dispersion of the high aspect ratio HNTs and the orientation of HNTs in PP matrix. Morphology studies show that HNTs can be dispersed in PP uniformly at lower HNTs loading and excessive loading of HNTs causes a little aggregation. Surface modification of HNTs can alleviate the aggregation effectively. The storage modulus of the nanocomposites increases consistently with the HNTs concentration. The surface modification is beneficial to the further improvement in storage modulus. Similar to other silicates, HNTs facilitate the crystallization of PP due to the heterogeneous nucleation.
Keywords: HALLOYSITE NANOTUBES (HNTS); POLYPROPYLENE (PP); NANOCOMPOSITE; REINFORCEMENT